Surgical treatment for severely damaged lung and pyothorax with bronchopleural fistula 9 years after induction chemoradiotherapy and bilobectomy - Hata, Yoshinobu (Oxford University Press, 2013)
Here, we present a 54-year old man 9 years after induction chemoradiotherapy and subsequent lower bilobectomy for Stage IIIA lung cancer suffering late complications of pyothorax and bronchopleural fistula in a severely damaged lung. Open-window thoracostomy and subsequent completion pneumonectomy via median sternotomy and anterior thoracotomy were performed. Although sternal wound infection required steel wire removal and debridement, with wound dressing at home, the patient could return to work. Late complications from infected treatment-damaged lungs need to be taken into consideration after induction chemoradiotherapy and subsequent surgery.